Implementation of Teaching Factory in Improving the Competence of Vocational High School Students (SMK) - Een Rohaeni; Sutaryat Trisnamansyah; Iim Wasliman; Supyan Sauri (Syntax Corporation Indonesia, 2021)
The problem of low absorption of vocational graduates is allegedly due to a gap between the competencies possessed by students and the needs in the world of work. The participation of the industrial world and the world of work in the learning process in SMK is still low. The general objective of this study is to identify and analyze the implementation of the teaching factory in improving the competence of vocational students. The specific objectives of this study are to determine: (1) planning of the teaching factory; (2) teaching factory organization; (3) implementation of teaching factory; (4) evaluation of teaching factory implementation; (5) partnership in teaching factory implementation; (6) problems and solutions in the implementation of the teaching factory; (7) the results obtained from the implementation of the teaching factory. The theoretical basis uses the management theory of G.R. Terry, and the policy foundation is Presidential Instruction No. 6 of 2016 concerning Vocational Revitalization, where the teaching factory is one of the strategies for implementing Vocational Revitalization. The study used a qualitative approach with descriptive data collection techniques through interviews, observations, and documentation studies. Testing the validity of the data is done through triangulation of sources and triangulation of methods. The results of the study stated that: 1) the planning of the teaching factory in the fields of curriculum, infrastructure and financing had been carried out well, but in the field of human resources it was necessary to plan for teacher competency improvement; 2) the organization of the teaching factory has been carried out well, but it is necessary to make a SOP (Standard Operating Procedure) for activities; 3) The implementation of the teaching factory has been running well, supported by Jobsheet devices, but verification and validation activities are needed for the Jobsheets used; 4) The teaching factory evaluation activities have been going very well; 5) Partnerships in teaching factories have been going well for Lemon Juice, Herbs way and Yoghurt products, but it is necessary to increase the number of industrial partners for other types of products; 6) Solutions to the problem of improving teacher competence are handled through internal internships in teaching factory activities and becoming supervisors for Industrial Work Practices; 7) The results obtained from the teaching factory implementation activities can increase the competence of hard skills and 78.26% of students' soft skills.